2019
DOI: 10.1002/cam4.2708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of locally advanced esophageal neuroendocrine carcinoma treated with chemoradiotherapy

Abstract: Background: Neuroendocrine carcinoma (NEC) arising from the esophagus (EsoNEC) is extreme rare, accounting for approximately 1% of esophageal cancer.Even for localized NEC, multidisciplinary approach including chemotherapy is recommended in treatment guidelines because of its high rates of systemic recurrence.However, it is controversial whether adding surgery or radiotherapy is appropriate local treatment for EsoNEC. There have been few reports regarding the clinical outcomes of definitive chemoradiotherapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Our study showed that both surgery and chemotherapy could significantly increase cancer‐specific survival of ENEC patients. According to previous studies, many centers recommend that chemotherapy should be the cornerstone of the treatment of ENEC 8,23 . A study from the Memorial Sloan‐Kettering Cancer Center suggested that for small cell ENEC patients treated with induction chemotherapy followed by consolidative chemoradiation can achieve long‐term survival, while the contribution of surgery was unclear 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that both surgery and chemotherapy could significantly increase cancer‐specific survival of ENEC patients. According to previous studies, many centers recommend that chemotherapy should be the cornerstone of the treatment of ENEC 8,23 . A study from the Memorial Sloan‐Kettering Cancer Center suggested that for small cell ENEC patients treated with induction chemotherapy followed by consolidative chemoradiation can achieve long‐term survival, while the contribution of surgery was unclear 24 .…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, many centers recommend that chemotherapy should be the cornerstone of the treatment of ENEC. 8 , 23 A study from the Memorial Sloan‐Kettering Cancer Center suggested that for small cell ENEC patients treated with induction chemotherapy followed by consolidative chemoradiation can achieve long‐term survival, while the contribution of surgery was unclear. 24 A recent nationwide study from Japan revealed that there was no significant difference in survival between the operative or non‐operative groups of stage I and II ENEC patients, and for stage III and IV ENEC, chemoradiotherapy led to significantly better prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy, such as irinotecan and platinum, is also among the first-line use. By now, multidisciplinary treatment, including adjuvant chemoradiotherapy, serves as an appropriate option, although ineffectiveness has been reported in large-cell ENEC concerning clinical outcomes ( 28 , 29 ). Besides, specific inhibition of molecules like CDK4/6 by using monoclonal antibody seems to be a promising strategy indicated by some cases ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the same AJCC guidelines for esophageal squamous cell carcinoma /adenocarcinoma are used for diagnosis and treatment[ 20 ]. Previous studies have demonstrated that surgery can extend the survival of esophageal NEC patients[ 21 ]. However, recent studies have shown that surgery may benefit only patients with early stage disease[ 6 , 13 ].…”
Section: Discussionmentioning
confidence: 99%